Comparing school choice and college admissions mechanisms by their strategic accessibility - Somouaoga Bonkoungou; Alexander Nesterov (Theoretical Economics, 2021)
Dozens of school districts and college admissions systems around the world have reformed their admissions rules in recent years. As the main motivation for these reforms, the policymakers cited the strategic flaws of the rules in place: students had incentives to game the system. However, after the reforms, almost none of the new rules became strategy-proof. We explain this puzzle. We show that the rules used after the reforms are less prone to gaming according to a criterion called "strategic accessibility": each reform expands the set of schools wherein each student can never get admission by manipulation. We also show that the existing explanation of the puzzle due to Pathak and Sönmez (2013) is incomplete.
Keywords: C78; D47; D78; 330; Market design; school choice; manipulability